Rice pest science and management : (International rice research institute, 1994)
Highlights of some of the research that has provided the basis for the implementation of integrated pest management (IPM) in rice, and some of the newer approaches and techniques that promise to contribute to improved pest management in this crop in the future, are outlined. In the first section of the book there are 9 papers that deal with different aspects of rice pest ecology and biology. The 3 papers in the second section are on the improvement and deployment of rice host plant resistance to pests. The final section of the book contains 6 papers on pest management in rice